Should opinion polls be illegal? - Sønderholm, Jørn (Politica, 2018)
The question of whether or not publication of opinion poll results should be illegal is of both theoretical and practical interest. A number of countries have laws in place that make the publication of opinion poll results illegal. The article concludes that there should be no legal restrictions on the publication of opinion poll results. The publication of such results should be legally permitted at any time during the electoral cycle. In the second section, a general line of thought centering on the moral nature of state coercion is presented in an attempt to show that the default position in the debate about the legality of the publication of opinion poll results ought be that the publication of such results should be legal. I argue i) that this general line of thought is convincing. There may, however, be at least one stronger argument in favor of the view that the publication of opinion poll results should be illegal. In the third section, I argue ii) that there is in fact no such argument. If i) and ii) are correct, then a very plausible case has been established for the conclusion of this article.